Iatrogenic Penile Amputation Due to Circumcision Clamp in an Eight-Year-Old Boy - Muhammad Baihaqy Ibnu Hakim; Taufiq Nur Budaya; Besut Daryanto (Jurnal Kedokteran Brawijaya, 2023)
The circumcision clamp has been the primary alternative to the traditional surgical circumcision procedure since its invention in 1934. The circumcision clamp has the following advantages such as improved wound healing, shorter operation time, and no stitch removal pain. However, the clamp technique has a disadvantage where the operator cannot visualize the glans penis. Many studies have already reported the incidence of trauma or psychiatric disorders related to penile amputation, but the case of circumcision clamp-related penile amputation in Indonesia had never been reported. An eight-year-old boy was taken to the emergency department with post-circumcision bleeding. The patient had been circumcised using an Anastomat® circumcision device in the clinic, two hours prior and then referred to the emergency department. We perform penile exploration, and a defect in the ventral part of the glans penis was found, with the source of bleeding coming from the glans penis, and the urethra remained intact. Penile degloving with urethral spatulation and catheterization with a 10 Fr 2-way foley catheter was installed, continued with penile reconstruction and skin closure. The operation lasted for about sixty minutes. After six months of follow-up, the patient could urinate normally and spontaneously without any clinical complaint. Even though circumcision using a circumcision clamp is considered a safe procedure and preferable to surgical circumcision nowadays, it is necessary to emphasize that the use of a circumcision clamp still has a risk rate for penile amputation.